Assessment of embryo morphology following perinatal exposure to aspirin, ibuprofen and paracetamol using whole embryo culture system. (12th December 2022) - Moungmaithong, Sakita; Leung, Bo Wah; Sahota, Daljit Singh; Wang, Chi Chui; Leung, Tak Yeung; Poon, Liona C.
Abstract: Background: Recent evidence from a meta-analysis indicates that maternal prenatal exposure, single or repeated, to non-steroidal anti-inflammatory drugs (NSAIDs) or non-opioid painkillers, is associated with increased risk of cerebral palsy and cognitive-behavioral disorders in offspring. One potential route of action is interference with the neurulation process and hence early brain development. Objective: To examine the effect of prenatal exposure to common NSAIDs and non-opioid drugs on neurulation using an in vitro whole embryo culture system. Methods: Mouse embryos from in-bred Institute of Cancer Research albino strain mice were exteriorized on embryonic day 7.5 and cultured for 48 h in either 1 mL heat-inactivated rat serum + 0.1% dimethyl sulfoxide ("Control") or 1 mL of rat serum supplemented with six increasing concentrations of laboratory-grade aspirin, paracetamol, and ibuprofen ("Experimental"). After culture, embryo morphological and developmental parameters were documented using standardized scoring systems at each dosage concentration. The assessed concentration in rat serum culture ranged from 1.23 to 13.57 mg/mL for aspirin and 0.06–4.93 mg/mL for paracetamol and ibuprofen. The equivalent respective human dosages were 600–6600 mg and 30–2400 mg. Results: Between-group comparisons ("Control" vs "Experimental") and post-hoc pair-wise tests, adjusted for multiple comparisons, indicating no statistically significant effect on crown-rump length ( p > .21), head length ( p > .28), somite number ( p > .25), incidence of absent hindlimb buds ( p > .18), yolk sac circulation score ( p > .07) and posterior neuropore closure ( p > .35) in the aspirin, paracetamol and ibuprofen experiments. All embryos had forelimb buds, closed anterior neuropores and none had neural tube defects. Conclusion: This study has demonstrated that there are no safety concerns regarding high-dose aspirin, ibuprofen, and paracetamol on mice's embryonic development.